Midnight Sun - Street scene - Arctic Circle - Finland ... - Campbell, Sandy (University of Alberta Library, 2011)
The \"midnight sun\", or the period when the sun does not set, begins in early June at the Arctic Circle. This photograph was taken at 0:14hrs in Rovaniemi. The patios were full of people enjoying the extended light and there were many cyclists on the streets. ...